Monarchy, Nation and the Common Good: Patriotism in Prussia, 1756-1806 - Sivonen, Jaakko, (History of European Political and Constitutional Thought ;, 2025)
This book provides a history of Prussian state patriotism from the Seven Years' War (1756-1763) until the Battle of Jena (1806). It argues that Prussian patriotism was not merely a prelude to German nationalism or a personality cult of Frederick the Great; rather, it was an inclusive and non-ethnic movement promoting ideals of citizenship, merit, and empowerment. Appealing to patriotism became a central method of promoting reform in a state governed by an absolute monarchy. Covering a turning point in early modern European intellectual history, this book provides a historical perspective for modern discussions on the relationship between patriotism and nationalism. See Less